PENGARUH PERSEPSI MAHASISWA AKUNTANSI MENGENAI LINGKUNGAN KERJA EKSTERNAL AUDITOR TERHADAP PILIHAN KARIERNYA SEBAGAI AKUNTAN PUBLIK : STUDI PADA PENERIMA BEASISWA DJARUM REGIONAL BANDUNG - Puti Kemala Tanjung, - (2011)
This research was aimed at finding out the influence of accounting students' perception about auditor's external working environment toward their choice of their future career as a public accountant. An instrument developed by Dezoort et al (1997) was employed as the indicator of the auditor's external working environment. The data were collected through a questionnaire given to accounting students who received scholarship from Djarum. The data were then analyzed by using Spearman Rank Correlation by employing SPSS version 16. The result of this research showed that the accounting students' perception about auditor's external working environment had no close correlation with their choice of their future career as a public accountant. Thus, it could be concluded that accounting students' perception about auditor's external working environment didn't really contribute to students' decision making of their future career as a public accountant.